1993
DOI: 10.1042/bj2910601
|View full text |Cite
|
Sign up to set email alerts
|

Isolation, characterization and localization of annexin V from chicken liver

Abstract: Annexin V has been purified from chicken liver; 40 mg of annexin V was obtained per kg of tissue. In contrast with mammalian liver, very little annexin VI was obtained. Surprisingly, chicken liver annexin V resembles mammalian annexin IV in its M(r) (32,500) and its isoelectric point (5.6), but amino-acid-sequence analysis demonstrates identity with chicken annexin V (anchorin CII). It binds to phospholipids in a Ca(2+)-dependent manner with free-Ca2+ concentrations for half-maximal binding to phosphatidylseri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
14
0

Year Published

1995
1995
2013
2013

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(17 citation statements)
references
References 58 publications
(65 reference statements)
3
14
0
Order By: Relevance
“…In addition, subcellular fractionation studies have shown that in heart, lung, liver, platelets and brain a proportion of the total annexin V remains associated with membranes even after extraction with EGTA. It is therefore likely that annexin V plays a role in the regulation of a membranelocalized process [7,8,[25][26][27][28]. We have demonstrated that, following physiological platelet activation, annexin V relocates from the cytosol and binds to membranes, which implicates annexin V in coupling increases in cytosolic [Ca# + ] to membranespecific processes [7,8].…”
Section: Introductionmentioning
confidence: 86%
“…In addition, subcellular fractionation studies have shown that in heart, lung, liver, platelets and brain a proportion of the total annexin V remains associated with membranes even after extraction with EGTA. It is therefore likely that annexin V plays a role in the regulation of a membranelocalized process [7,8,[25][26][27][28]. We have demonstrated that, following physiological platelet activation, annexin V relocates from the cytosol and binds to membranes, which implicates annexin V in coupling increases in cytosolic [Ca# + ] to membranespecific processes [7,8].…”
Section: Introductionmentioning
confidence: 86%
“…This protein recognizes APL on the platelet surface and is used as a nonquantitative probe (6)(7)(8). In recent years it has been described as detecting PS exposure, although several annexins also bind PE (6,(9)(10)(11)(12)(13). Other proteins that indirectly measure APL exposure include lactadherin and cinnamycin, reported as specific PS or PE indicators, respectively (14)(15)(16).…”
mentioning
confidence: 99%
“…They are usually considered as soluble calcium dependent phospholipid binding proteins but recent reports have suggested that they could also be tightly associated with cellular membranes (Sheets et al 1987, Valentine-Braun et al 1987, Campos-Gonzales et al 1989, Pula et al 1990, Bianchi et al 1992, Boustead et al 1993, Futter et al 1993, Tagoe et al 1994, Bohm et al 1994, Trotter et al 1994, Blanchard et al 1996, Liu et al 1997, Harder et al 1997, Jost et al 1997, Turpin et al 1998. Annexins have a common structure consisting of a core domain of four or eight repeated sequences containing calcium and phospholipid binding sites.…”
mentioning
confidence: 99%